2005
DOI: 10.1074/jbc.m508451200
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Transmembrane Domain of FXYD7 in Structural and Functional Interactions with Na,K-ATPase

Abstract: Members of the FXYD family are tissue-specific regulators of the Na,K-ATPase. Here, we have investigated the contribution of amino acids in the transmembrane (TM) domain of FXYD7 to the interaction with Na,K-ATPase. Twenty amino acids of the TM domain were replaced individually by tryptophan, and combined mutations and alanine insertion mutants were constructed. Wild type and mutant FXYD7 were expressed in Xenopus oocytes with Na,KATPase. Mutational effects on the stable association with Na,KATPase and on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
3
11
0
Order By: Relevance
“…As shown in this study, phosphorylation of PLM by PKA or PKC does not influence the effect of PLM on the K ϩ affinity of Na,K-ATPase ␣1/␤1 and ␣2/␤1 isozymes. The lack of an effect of PLM phosphorylation on the apparent K ϩ affinity of Na,K-ATPase is consistent with our previous observation that the effect of several FXYD proteins on the K ϩ affinity is mainly determined by interactions in the transmembrane domains of the two proteins (38,39), which may not be influenced by modifications in the cytoplasmic domain of PLM.…”
Section: Discussionsupporting
confidence: 77%
“…As shown in this study, phosphorylation of PLM by PKA or PKC does not influence the effect of PLM on the K ϩ affinity of Na,K-ATPase ␣1/␤1 and ␣2/␤1 isozymes. The lack of an effect of PLM phosphorylation on the apparent K ϩ affinity of Na,K-ATPase is consistent with our previous observation that the effect of several FXYD proteins on the K ϩ affinity is mainly determined by interactions in the transmembrane domains of the two proteins (38,39), which may not be influenced by modifications in the cytoplasmic domain of PLM.…”
Section: Discussionsupporting
confidence: 77%
“…It was further demonstrated that three transmembrane residues are particularly important for the physical interaction of FXYD5 with the pump. Taken together with previous data on other FXYD proteins (23,24,26), it appears that different FXYD proteins interact similarly with the Na ϩ -K ϩ -ATPase and their different functional effects are likely to stem from a small number of key residues.…”
Section: Discussionmentioning
confidence: 68%
“…33) Two-thirds of the face of the transmembrane helix in FXYD-7, which contains the conserved two Gly residues, was suggested to be important for both structural and functional interaction with the Na ϩ /K ϩ -ATPase a subunit. 34) Since a buried Gly residue has the smallest average volume, 35) these conserved Gly residues would form a hollow for suitable interaction between transmembrane helices of integral membrane proteins.…”
Section: Discussionmentioning
confidence: 99%